PENGGUNAAN MEDIA SANK MAGIC BOOK UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS II SDN 06/VI PAMENANG KABUPATEN MERANGIN - Hairun Nisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the lack of learning motivation in Mathematics among second-grade students at SD Negeri 06 Pamenang, evidenced by their limited attention, participation, and enthusiasm during lessons. One contributing factor was the use of conventional instructional media, which failed to engage the students. The study aimed to describe the use of the "Sank Magic Book" as an instructional medium in Mathematics and to assess the resulting improvement in student learning motivation. A Classroom Action Research (CAR) design utilizing a mixed-methods approach was employed across two cycles, comprising the phases of planning, action implementation, observation, and reflection. The participants consisted of 21 second-grade students from SD Negeri 06 Pamenang. Data were collected through observation, questionnaires, interviews, and documentation. The findings indicate that the use of the Sank Magic Book effectively enhanced student learning activity and motivation. Questionnaire results showed that learning motivation increased from 32.00% in the pre-cycle stage to 54.20% in Cycle I, rising further to 82.69% in Cycle II. Learning activity also improved, increasing from 45.00% in the pre-cycle stage to 85.20% in Cycle II. Thus, the Sank Magic Book proved effective in boosting Mathematics learning motivation among the second-grade students at SD Negeri 06 Pamenang.